PEMBERDAYAAN PEREMPUAN MANDIRI DENGAN TEKNOLOGI DIGITAL MARKETING DI GAMPONG SUKAJADI KEBUN IRENG KECAMATAN LANGSA LAMA KOTA LANGSA - Tengku Putri Lindung Bulan; Suri Amilia; Ziaul Maula (LPPM dan PM Universitas Samudra, 2021)
Conditions in the midst of the Covid-19 pandemic have an impact for women. Women must be able to empower themselves optimally so that they can provide added value to the family. This community service activity was carried out at Gampong Sukajadi Kebun Ireng Kecamatan Langsa Lama Kota Langsa which aims: (1) to provide socialization to housewives about the use of internet technology and the use of digital marketing technology-based marketing methods, (2) to provide motivation utilization of marketing methods based on digital marketing technology for entrepreneurship, and (3) assistance in making online sales media. This socialization activity was carried out using the lecture method, direct practice, and discussion and question and answer. This activity ends with an evaluation of the program of activities. The evaluation of this service activity was carried out by the PKM Team together with the community and the Sukajadi Kebun Ireng Village apparatus. The result achieved is that community service activities run well and smoothly. This can be seen from the enthusiasm and enthusiasm of the participants in participating in the socialization. Village officials and housewives were very active and involved during this socialization activity because they wanted to become strong, independent and prosperous women in order to help the family economy.